Controlador adaptativo preditivo robusto por modelo de referência aplicado a conversores estáticos conectados à rede de energia elétrica - Silveira, Wagner Barreto da (2021)
In this work, a discrete-time Robust Adaptive Predictive Model Reference Controller is presented. The topology is based on the combination of the adaptive structure of Robust Model Reference Adaptive Controller (RMRAC), for real time gain adjustment, with the One-Sample Ahead Preview controoler (OSAP), which is a particular case of Model Predictive Control (MPC). The proposed controller is applied for the grid-side current control of a grid-tied voltage-source inverter (VSI). The proposal has as main objectives: To intrinsically compensate the transport delay present in DC/AC converters through the predictive structure; Reduce the computational burden needed to calculate n future plant predictions and control action typical of MPC controller; Reduce the computational effort needed to calculate n gains from RMRAC controller considering a modeled part of the plant and the reduced order reference model. Finally, perform an active damping of the LCL filter resonance, avoiding instability problems and/or poor performance. Simulation and experimental results are presented to validate the controller performance.